2022
DOI: 10.1097/gme.0000000000001960
|View full text |Cite
|
Sign up to set email alerts
|

Clinical suspicion of sarcopenic obesity and probable sarcopenic obesity in Colombian women with a history of surgical menopause: a cross-sectional study

Abstract: Objectives: To identify the frequency of clinical suspicion of sarcopenic obesity (CSSO) and probable sarcopenic obesity (PSO) and to estimate the association between them and surgical menopause.Methods: A cross-sectional study carried out in women residing in Colombia, ages 60 to 75 years. Body mass index, the SARC-F scale, SARC-CalF < 31, and SARC-CalF <33 versions adding the calf circumference measurement in the last two were used to identify CSSO. Muscle strength measurement was added to the above measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…This is an excellent segue into the topic of the study in the current issue 1 . The same review of PubMed showed the first mention of sarcopenic obesity in 1996 with 1,026 citations through January, 2022.…”
Section: Sarcopenic Obesitymentioning
confidence: 85%
See 3 more Smart Citations
“…This is an excellent segue into the topic of the study in the current issue 1 . The same review of PubMed showed the first mention of sarcopenic obesity in 1996 with 1,026 citations through January, 2022.…”
Section: Sarcopenic Obesitymentioning
confidence: 85%
“…As the authors point out 1 individuals being over 60 years of age, sedentary lifestyle, high-fat diet, high alcohol consumption, and smoking all increase the likelihood of developing sarco-penic obesity. They also astutely point out sarcopenic obesity is associated with several comorbidities including increased insulin resistance, diabetes, cardiovascular disease, metabolic syndrome, dyslipidemia, arterial hypertension, stress, suicidal ideation, knee osteoarthritis, reduced coordination, or aerobic capacity, osteoporosis, fractures, and even all-cause mortality 17 …”
Section: Sarcopenic Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…Although several cut-off points are indicated for assessing muscle strength, <16.0 kg was used, as suggested in the EWGSOP2 criteria. 12,13,29,30 Two measurements were established for PS:…”
Section: Methodsmentioning
confidence: 99%